(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to determine the influence of wearing high heeled shoes over the spinal arrangement. Twenty healthy women (age = 24,0 ± 4,0 years and BMI = 21,1 2,0 kg/m²) were valued. Posture was determined by photometry in two instants, i.e., with (9.0 cm) and without high heeled shoes. The spinal processes of C7, T12, L5 and the acromium were identified and marked over the skin. The used methods has been long applied by Christie et al. (1995) and Braun & Amundson (1989). Shoulder angle increased (p<0.05) when participants wore high heeled shoes. Head and C7 horizontal displacement also changed in response to shoe use and significant changes were found (p<0.05). The use of high heeled shoes did not cause changes in the curves of the spine. However, changes in the horizontal displacement of the upper markers suggest the use of a more flexed posture of the vertebral column. It is suggested that small internal changes in several levels of the spine contributed to changes in posture, although such changes were not translated in terms of angular variations that are generally used to determine posture.